Confessional pluralism in Central and Eastern Europe – a GIS approach - Csikós, Nándor; Máté-Tóth, András (Geographica Pannonica, 2023)
In this recent study, we analyse the religious diversity of Central and Eastern Europe, from the Balkans up to the Baltic region. This region has many religious confessions, without claiming completeness, Roman Catholic, Reformed, Lutheran, Orthodox, Islam, Hussite and many people without any religion. The recent spatial distribution of the religious confessions has been shaped by different drivers across Central and Eastern Europe. We chose a quantitative method to visually interpret the pluralism of the religious confessions and we selected diversity indices. We calculated the diversity of the religious confessions and ethnicities in a very detailed resolution, at municipality level of each country, based on population census data of 2011. We found statistically significant relationship between the diversity of religious confessions and the diversity of ethnicities. We have also shown that near the national borders, the religious pluralism is higher than in another areas. There is statistically significant connection between the former national borders (1900s and 1930s) and the religiously plural areas. The results of this study provide the evidence of the spatial distribution of borderline syndrome and serves as a good basis for further research (theoretical and statistical) of the religion pluralism in Central-Eastern Europe.
Keywords: religious pluralism; religious diversity; GIS; borderline; religion; statistical analysis